Cost effective and adaptable measures of estimation of visceral adiposity - Divya Elizabeth Mathew; Jonathan Arul Jeevan Jayakaran; Samuel George Hansdak; Ramya Iyadurai (Clinical Epidemiology and Global Health, 2023)
Background: Obesity is a major public health problem these days. Obesity, specifically visceral adiposity is linked to insulin resistance and an increased risk of cardiometabolic diseases. Measurement of visceral adiposity helps to understand the prevalence of obesity disorders and strategize interventions targeting its reversal. Methods: A literature search was done to identify studies that looked at the quantification and estimation of visceral adiposity published from January 1990 to May 2023. Online databases PubMed, Google Scholar, Scopus were used for the literature search. Findings: Various cost-effective methods are available for the estimation of visceral adiposity. Simple anthropometric measurements like the waist circumference and waist-to-height ratio are useful to estimate visceral adiposity during a routine clinical examination. The novel Metabolic score for Visceral Fat Estimation (METS-VF) has the potential for widespread clinical use but remains to be validated in different populations. Ultrasound-based estimation of visceral adiposity strongly correlates with quantification by MRI. However, it is operator dependent and requires strict adherence to established measurement protocols. Conclusion: Anthropometric measurements of waist circumference, waist-to-height ratio, the METS-VF score, BIA, and USG-based assessment of visceral and ectopic fat depots are potentially cost-effective and adaptable measures of estimation of visceral adiposity.